Incorporation of CT‐based measurements of trunk anatomy into subject‐specific musculoskeletal models of the spine influences vertebral loading predictions - Bruno, Alexander G.; Mokhtarzadeh, Hossein; Allaire, Brett T.; Velie, Kelsey R.; De Paolis Kaluza, M. Clara; Anderson, Dennis E.; Bouxsein, Mary L. (Journal of orthopaedic research, 2017)
ABSTRACT We created subject‐specific musculoskeletal models of the thoracolumbar spine by incorporating spine curvature and muscle morphology measurements from computed tomography (CT) scans to determine the degree to which vertebral compressive and shear loading estimates are sensitive to variations in trunk anatomy. We measured spine curvature and trunk muscle morphology using spine CT scans of 125 men, and then created four different thoracolumbar spine models for each person: (i) height and weight adjusted (Ht/Wt models); (ii) height, weight, and spine curvature adjusted (+C models); (iii) height, weight, and muscle morphology adjusted (+M models); and (iv) height, weight, spine curvature, and muscle morphology adjusted (+CM models). We determined vertebral compressive and shear loading at three regions of the spine (T8, T12, and L3) for four different activities. Vertebral compressive loads predicted by the subject‐specific CT‐based musculoskeletal models were between 54% lower to 45% higher from those estimated using musculoskeletal models adjusted only for subject height and weight. The impact of subject‐specific information on vertebral loading estimates varied with the activity and spinal region. Vertebral loading estimates were more sensitive to incorporation of subject‐specific spinal curvature than subject‐specific muscle morphology. Our results indicate that individual variations in spine curvature and trunk muscle morphology can have a major impact on estimated vertebral compressive and shear loads, and thus should be accounted for when estimating subject‐specific vertebral loading. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2164–2173, 2017. We created subject‐specific models of the thoracolumbar spine to determine how sensitive vertebral loading estimates are to variations in spine curvature and muscle morphology measured from computed tomography (CT) scans. Vertebral compressive loads predicted by subject‐specific models varied between 54% lower and 45% higher than those estimated using models adjusted only for subject height and weight and were more sensitive to spinal curvature than muscle morphology. Individual variations in spine curvature and muscle morphology should be accounted for when estimating spinal loading.